Optimization of the Coagulation-flocculation Process Using Ferric Chloride and Phosphate for the Reduction of Contaminants in the Slaughterhouses Wastewater - Nuñez, A.W. Pilco-; Palacio, K.M. Zevallos; Campos, A.Z. García; Salinas, J.A. Flores; Pisfil, J.A. Montaño; Farfan, R.E. Solis; Perez, S.A Trujillo; Paz, A. Arroyo-; García, J.A. Poma (International Journal of Membrane Science and Technology, 2023)
In this work, the coagulation-flocculation process was optimized using ferric chloride and phosphate for the reduction of pollutants in the wastewater from the Conchucos S.A., Lima. Parameters were measured in percentage reduction of chemical oxygen demand (COD), turbidity (NTU) and total phosphorus (PT mg/L), adding ferric chloride as coagulant and potassium dihydrogen phosphate as flocculant. The effects of four independent variables were investigated: ferric chloride dose (500-700 ppm), phosphate dose (700-900 mg/L), fast agitation speed (250-320 rpm) and slow agitation speed (90-100 rpm). The experimental data were optimized by the response surface method using a central composite design. The results show that the statistical models obtained F-values of 3.33, 4.27 and 4.16 for the percent reduction of COD, turbidity and total phosphorus, respectively. Furthermore, the statistical models developed to predict the responses were confirmed by significant probability values (p<0.05). On the fit of the models, an R2 of 0.61, 0.66 and 0.67 are shown for COD, turbidity and total phosphorus percentage, respectively. The optimum conditions were found experimentally at 700 ppm of ferric chloride dose, 900 ppm of phosphate, 320 rpm fast speed and 100 rpm for a reduction of 75.46% of COD, 83.47% of turbidity and 44.08% of total phosphorus presenting a desirability of 0.7.